2018
DOI: 10.1002/jcp.26745
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage protection in Ctsk‐/‐ mice is associated with cellular and molecular changes in subchondral bone and cartilage matrix

Abstract: Osteoarthritis (OA) is a degenerative disease and a major cause of chronic disability in aging individuals. Cathepsin K (CatK), encoded by the Ctsk gene, has been implicated in the pathogenesis of pycnodysostosis and osteoporosis. The use of a selective inhibitor of CatK was recently shown to delay OA progression in rabbits. However, the cellular mechanisms underlying these protective effects remain unexplored. We examined articular cartilage maintenance and joint bone remodeling using Ctsk null mice (Ctsk ) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…One of the key enzymes expressed by osteoclasts for bone resorption is cathepsin K (CTSK). Ctsk knockout mice (Ctsk −/− ) maintained cartilage volume and structure in OA surgical model of destabilization of the medial meniscus (DMM model), although the TRAP + osteoclast population in subchondral bone was increased in both wild type and Ctsk −/− mice (Soki et al, 2018), and the subchondral bone was also preserved in OA Ctsk −/− mice (Soki et al, 2018).…”
Section: Osteoclasts and Osteoclastogenesis In Subchondral Bone Resorptionmentioning
confidence: 99%
“…One of the key enzymes expressed by osteoclasts for bone resorption is cathepsin K (CTSK). Ctsk knockout mice (Ctsk −/− ) maintained cartilage volume and structure in OA surgical model of destabilization of the medial meniscus (DMM model), although the TRAP + osteoclast population in subchondral bone was increased in both wild type and Ctsk −/− mice (Soki et al, 2018), and the subchondral bone was also preserved in OA Ctsk −/− mice (Soki et al, 2018).…”
Section: Osteoclasts and Osteoclastogenesis In Subchondral Bone Resorptionmentioning
confidence: 99%
“…Previous studies have reported an increased expression of cathepsin K in human OA cartilage and chondrocytes, as compared to healthy cartilage and chondrocytes 13 . They also demonstrated that OA progression was delayed in cathepsin K knockout mice using a surgical OA model 17,18 . Several other studies have reported that inhibition of cathepsin K resulted in reduced cartilage degeneration and inflammation in mouse OA models and collagen-induced arthritis [19][20][21] .…”
Section: Discussionmentioning
confidence: 95%
“…And this is similar to our findings. Additionally, experimental studies have confirmed that CTSK −/− mice exhibit a reduction in the remodeling of subchondral bone and calcified cartilage in the destabilization of the medial meniscus induced OA [38]. TIMP1 belongs to TIMP gene family, which encodes a protein that is a natural inhibitor of matrix metalloproteinase (MMP) involved in the pathology of OA [39].…”
Section: Discussionmentioning
confidence: 99%